Faculty Workload and Well-being at President Ramon Magsaysay State University: Impacts of Allied Tasks on Stress and Health - Vizcarra, Myra Liza O.; Aragon, Almay Elena A.; Tiangco, Peter-Vir V.; Basarte, Charie A. (Future Science / FSH-PH Publications, 2024)
Faculty members in higher education institutions are increasingly burdened by a growing workload, particularly non-teaching assignments or allied tasks. The time spent on workloads were observed to have increased in the past years. Hence, the researchers decided to undertake this study entitled,”Faculty Workload and Well-being at President Ramon Magsaysay State University: Impacts of Allied Tasks on Stress and Health,” during the academic year 2021-2022. A quantitative descriptive design was employed to evaluate the variables of the study. A researcher-made survey questionnaire was administered to forty-three faculty members using population sampling. Data were collected through online platform due to limited face to face interactions. A letter of consent was emailed to the three(3) Campus Directors of north campuses prior the online survey. Descriptive statistics such as percentage, weighted means, and Pearson Correlation was used in the treatment of data. The findings revealed that on average, faculty members spent approximately 29.54 hours on teaching tasks and 34.73 hours on allied tasks per week. This study revealed significant differences in the time spent on allied tasks across various demographic groups, such as age, gender, civil status, highest educational attainment, and length of service. Additionally, a significant relationship was found between the time spent on teaching and allied tasks and the extent of experienced stress, but not on personal life, mental health, or physical health. Based on these findings, it is recommended that the university administration implement strategies such as offering mental health support services and creating a more supportive work environment. Reallocating administrative responsibilities or hiring support staff is highly encouraged. Providing health breaks may also be implemented which could help address stress.